Coder and decoder of fractal signals of comb-type structure - Politanskyi, R. L.; Veryga, A. D. (Technology and design in electronic equipment, 2014)
The article presents a coder and decoder of fractal signals of comb-type structure (FSCS) based on microcontrollers (MC). The coder and decoder consist of identical control modules, while their managed modules have different schematic constructions. The control module performs forming or recognition of signals, and also carries out the function of information exchange with a computer. The basic element of the control module is a PIC18F2550 microcontroller from MicroChip. The coder of the system forms fractal signals of a given order according to the information bits coming from the computer. Samples of the calculated values of the amplitudes of elementary rectangular pulses that constitute the structure of fractal pulses are stored in the memory of the microcontroller as a table. Minimum bit capacity of the DAC necessary for the generation of FSCS of fourth order is four bits. The operation algorithm, "wired" into the controller of the program, provides for encoding of the transmitted information by two-bit symbols. Recognition of the start of transmission of each byte in the communication channel is performed by the transmission of the timing signal.In a decoder the microcontroller carries out reception and decoding of the received fractal signals which are then transmitted to the computer. The developed algorithm of the program for the microcontroller of the decoder is carried out by determination of order of fractal impulse after the value of sum of amplitudes of elementary impulses, constituents of fractal signal.The programs for coder and decoder are written in "C". In the most critical places of the program influencing on the fast-acting of chart “assembler” insertions are done.The blocks of the coder and decoder were connected with a coaxial 10 meters long cable with an impedance of 75 Ohm. The signals, generated by the developed coder of FSCS, were studied using a digital oscillograph. On the basis of the obtained spectrums, it is possible to draw a conclusion, that the fractal signals formed by the coder are wideband and can be used in noise-resistant and protected communication systems.